Qualitative, quantitative, and antimicrobial activity variations of the essential oils prepared from Thymus vulgaris and Micromeria fruticosa samples subjected to different drying conditions. - Alqarni, Mohammed; Alsalgini, Ayman; Abujheisha, khalil; Daghar, Mohammed; Alkhuraif, Fahd; Abedel kader, Maged (Arabian Journal for Science and Engineering, 2022)
The treatment of plant materials after collection may affect their volatile components. Three aliquots of Thymus vulgaris and Micromeria fruticosa representing fresh, freeze- and shade-dried samples were subjected to hydrodistillation to obtain essential oil. Qualitative and quantitative study of the essential oils and their antimicrobial activity was performed. GC–MS analyses are used to identify the oil components based on relative retention indexes and MS comparison through NIST library. Antimicrobial activities against E. coli, P. aeruginosa, S. aureus, B. cereus and C. albicans were studied. Little decrease in oil contents was observed in freeze-dried plant samples while shade drying resulted in dramatic loss of the oils contents. The percentage of the major components were affected by the various treatment conditions. Applied vacuum in the freeze-dried samples resulted in loss of the more volatile components. Shade drying leads to slow decrease in moisture contents and permits enzymatic activity resulting in large changes in the percentage of some components in M. fruticosa such as pulegone and β-caryophyllene. The oil samples from both plants expressed better activity against P. aeruginosa and C. albicans. The level of antimicrobial activities was equal in all oil samples.
Keywords: GC–MS · Thymus vulgaris · Micromeria fruticose · Essential oil · Drying · Antimicrobial